Dysfibrinogenemia and hypofibrinogenemia - Spectrum of pathogenic variants in Slovak patients - Jaraskova, Dominika; Chandoga, Jan; Batorova, Angelika; Prigancova, Tatiana; Juhosova, Miriama; Durina, Pavol; Vavrova, Alzbeta; Dallemule, Silvia; Petrovic, Robert; Kyselova, Anna; Jankovicova, Denisa; Bohmer, Daniel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
INTRODUCTION: Congenital hypofibrinogenemia (CH) and congenital dysfibrinogenemia (CD) are rare coagulation disorders caused by quantitative or qualitative defects in the fibrinogen gene. The aim of this study was to characterize the genetic background and the clinical manifestations of congenital fibrinogen disorders in the patients from Slovakia registered at the National Haemophilia Centre. MATERIALS AND METHODS: Results of genetic analysis of the fibrinogen genes FGA, FGB and FGG using polymerase chain reaction followed by direct sequencing were evaluated in 36 patients. RESULTS: Molecular-genetic analysis revealed six novel variants - FGA c.923_968dup p.(Gly324Lysfs*44) and FGG c.1105C>T p.(His369Tyr) were identified in CD patients. In CH patients, in the FGG gene c.8G>A p.(Trp3*), c.823G>T p.(Glu275*) and c.323C>A p.(Ala108Asp) variants were detected. In the FGB gene c.1427C>T p.(Ser476Leu) was identified. CONCLUSION: This study is a positive contribution towards expanding knowledge about genetic variants in patients with congenital fibrinogen disorders.
Keywords: FGB; hypofibrinogenemia; dysfibrinogenemia; FGA; FGG